Mixed infection by two West African tomatoinfecting begomoviruses and ageratum leaf curl Cameroon betasatellite in tomato in Cameroon - Leke, W.; Kvarnheden, A. (Springer, 2014)
Begomovirus isolates ToF3B2 and ToF3B17and betasatellite isolate SatBToF3 were obtained from thesame infected tomato plant showing begomovirus diseasesymptoms in Fontem, Cameroon. The full-length nucleotidesequences of ToF3B2, ToF3B17 and SatBToF3 werecloned and sequenced and were determined to be 2,797 nt,2,794 and 1,373 nt long respectively. When compared withother begomovirus and betasatellite sequences, ToF3B2was 93.5 % identical to Tomato leaf curl Togo virus,ToF3B17 was 95 % identical to Tomato leaf curl Cameroonvirus and SatBToF3 was 92 % identical to Ageratumleaf curl Cameroon betasatellite (ALCCMB), respectively.The identification of ALCCMB in Ageratum and now intomato strongly suggests Ageratum may be an alternativehost to these viruses and that ALCCMB is non host specificand may cause severe diseases when transmitted to othercrops.